THE ENGLISH LEARNING ASSISTANCE BY PARENTS OF ELITE ELEMENTARY SCHOOL STUDENTS IN YOGYAKARTA - Dinar Martia Azizah (JELLT (Journal of English Language and Language Teaching), 2022)
Although previous research has revealed that parental learning assistance can support children's English language skills, only a few of these studies have been conducted in Indonesia. Therefore, the purpose of this study is to describe (1) the motivation of parents in introducing English from an early age, and (2) the manifestation of assistance in learning English by parents. This research is a case study conducted in an elite elementary school in Yogyakarta where the students have good speaking skills and achievements in English competitions. Data were collected by using an open questionnaire given to 60 parents of grade III-VI, then it was analyzed through data condensation, data presentation, and drawing conclusions. The results showed that parents introduced English from an early age because of the belief that the younger a person learns the language, the easier it is to master and the hope that mastering English can support children's education and careers in the future. The manifestation of assistance in learning English is carried out to develop listening, speaking, reading, and writing skills. Keywords: learning assistance, parents, English, elite elementary school